Controversial Policy Seeking Balance Between Savings and Basic Needs - Putri, Dewa Ayu Made Dyana (Indonesian Journal of Law and Justice, 2025)
This study explores the impact of the controversial budget efficiency policy implemented by the Indonesian government in 2025, focusing on the education and health sectors. Through in-depth analysis, this study reveals how policies aimed at reducing waste have the potential to hinder the realization of the goal of developing superior and healthy human resources. Budget cuts in the education sector raise concerns about disrupted access to education for the underprivileged, declining quality of education, and threatening the welfare of educators. Meanwhile, budget cuts in the health sector have the potential to reduce people's access to adequate health services, especially in remote areas. This study also highlights the plan for the Minerba Bill which grants permission to universities to manage mines. This policy, which is claimed as an alternative funding solution for universities, raises questions about academic independence and the potential shift in the function of education in Indonesia.